Amyloid-β protein oligomerization and the importance of tetramers and dodecamers in the aetiology of Alzheimer's disease. - Bernstein, S; Dupuis, N; Lazo, N; Wyttenbach, T; Condron, M; Bitan, G; Teplow, D; Shea, J; Ruotolo, B; Robinson, C; Bowers, M (2009)
In recent years, small protein oligomers have been implicated in the aetiology of a number of important amyloid diseases, such as type 2 diabetes, Parkinson's disease and Alzheimer's disease. As a consequence, research efforts are being directed away from traditional targets, such as amyloid plaques, and towards characterization of early oligomer states. Here we present a new analysis method, ion mobility coupled with mass spectrometry, for this challenging problem, which allows determination of in vitro oligomer distributions and the qualitative structure of each of the aggregates. We applied these methods to a number of the amyloid-β protein isoforms of Aβ40 and Aβ42 and showed that their oligomer-size distributions are very different. Our results are consistent with previous observations that Aβ40 and Aβ42 self-assemble via different pathways and provide a candidate in the Aβ42 dodecamer for the primary toxic species in Alzheimer's disease.